Communicating the True Meaning of Modern Masculinity through the Mister Supranational Thailand - Plodmusik, Worapong (Arts of Management Journal, 2024)
This research delves into the contemporary discourse on masculinity, with a focus on the communication strategies employed within the framework of Mister Supranational Thailand. It aims to investigate the research activities surrounding them as a contextual backdrop. Employing qualitative methodologies, particularly in-depth research, the study examines news coverage and communication practices related to masculinity stemming from research activities conducted between 2016 and 2023. The research cohort comprises 13 individuals categorized into three groups: group 1 consists of 7 contest winners; group 2 comprises 3 contest organizers; and group 3 encompasses organizations or individuals consistently sending contestants consecutively over three years, totaling 3 individuals. Analysis of the data reveals that within the realm of modern masculinity communication, winners of the Mr. Supranational Thailand contest underscore the significance of possessing knowledge, intellect, and charisma, as these qualities serve as defining attributes of modern masculinity, epitomizing the archetype of the "smart, charming man." Furthermore, physical appearance is acknowledged as a pivotal aspect of personal identity, influencing the success of contest participants. Secondary elements, such as personality traits and attire, are also deemed noteworthy. In terms of fostering a nuanced understanding of contemporary masculinity, emphasis is placed on self-discovery and inspiration, facilitating societal acceptance of diversity. Pageant activities emerge as crucial platforms for disseminating ideals of modern masculinity, serving concurrently as vehicles for brand marketing and bolstering the reputations of contest victors.